A new mutation of congenital methemoglobinemia exacerbated after methylene blue treatment. Issue 2 (15th February 2018) - Yamaji, Fuminori; Soeda, Akio; Shibata, Hiroki; Morikawa, Takuya; Suzuki, Kodai; Yoshida, Shozo; Ogura, Shinji
Abstract : Case: Methylene blue is useful for the treatment of methemoglobinemia. However, even after the patient's methemoglobin (metHb) rate has improved, careful observation is important because they could have undiagnosed congenital methemoglobinemia. In this case, a 67‐year‐old man underwent gastrointestinal endoscopy with the use of lidocaine for local anesthesia. During the examination, he complained of dyspnea and had low SpO2 despite normal PaO2 and SaO2 . He was transferred to our department as a suspected case of acquired methemoglobinemia. Outcome: The patient's metHb level was 26.2%. We administered methylene blue i.v. and his metHb level subsequently decreased to 1.6%. However, his metHb level gradually increased to 18.2%, and we suspected that he had congenital methemoglobinemia. We administered riboflavin and ascorbic acid orally, and his metHb level decreased to 6.4%. We also obtained genomic DNA from the patient and identified a novel variant of CYB5R3 . Conclusion: We report a novel variant of congenital methemoglobinemia that deteriorated after methylene blue treatment. Abstract : We report a novel variant of CYB5R3 gene congential methemoglobinemia deteriorated after methylene blue treatment.